Spray drying of drug-swellable dispersant suspensions for preparation of fast-dissolving, high drug-loaded, surfactant-free nanocomposites. (3rd October 2015) - Azad, Mohammad; Arteaga, Colby; Abdelmalek, Beshoy; Davé, Rajesh; Bilgili, Ecevit
Abstract: Bioavailability of a poorly soluble drug can be improved by preparing a drug nanosuspension and subsequently drying it into nanocomposite microparticles (NCMPs). Unfortunately, drug nanoparticles aggregate during milling and drying, causing incomplete recovery and slow dissolution. The aim of this study is to investigate the impact of various classes of dispersants on drug dissolution from drug NCMPs, with the ultimate goal of enhancing the bioavailability of poorly water-soluble drugs via high drug nanoparticle loaded, surfactant-free NCMPs. Precursor suspensions of griseofulvin (GF, model drug) nanoparticles in the presence of various dispersants were prepared via wet stirred media milling and spray dried to form the NCMPs. Hydroxypropyl cellulose (HPC, polymer) alone and with sodium dodecyl sulfate (SDS, surfactant) was used as a base-line stabilizer/dispersant during milling. Two swellable crosslinked polymers, croscarmellose sodium (CCS) and sodium starch glycolate (SSG), and a conventional soluble matrix former, Mannitol, were used in addition to HPC. Besides being used as-received, CCS was also wet co-milled with GF for two different durations to examine the impact of CCS particle size. Laser diffraction, scanning electron microscopy, powder X-ray diffraction (XRD), UV spectroscopy, NCMP redispersion and dissolution tests were used for characterization. The results show that incorporation of CCS/SSG, preferably wet-milled to a wide particle size distribution, into the spray-dried NCMPs resulted in fast release and dispersion of drug nanoparticle clusters. The swellable dispersants were superior to Mannitol in dissolution enhancement, and could achieve fast release comparable to SDS, demonstrating the feasibility of spray drying to prepare high drug-loaded, surfactant-free nanocomposites.